Case Report: Addition of PD-1 Antibody Camrelizumab Overcame Resistance to Trastuzumab Plus Chemotherapy in a HER2-Positive, Metastatic Gallbladder Cancer Patient - Wang, Li; Li, Xiaomo; Cheng, Yurong; Yang, Jing; Liu, Si; Ma, Tonghui; Luo, Li; Hu, Yanping; Cai, Yi; Yan, Dong (Frontiers in Immunology, 2022)
HER2 amplification/overexpression is a common driver in a variety of cancers including gallbladder cancer (GBC). For patients with metastatic GBC, chemotherapy remains the standard of care with limited efficacy. The combination of HER2 antibody trastuzumab plus chemotherapy is the frontline treatment option for patients with HER2-positive breast cancer and gastric cancer. Recently, this regime also showed antitumor activity in HER2-positive GBC. However, resistance to this regime represents a clinical challenge. Camrelizumab is a novel PD-1 antibody approved for Hodgkin lymphoma and hepatocellular carcinoma in China. In this study, we presented a HER2-positive metastatic GBC patient who was refractory to trastuzumab plus chemotherapy but experienced significant clinical benefit after the addition of camrelizumab. Our case highlights the potential of immunotherapy in combination with HER2-targeted therapy in HER2-positive GBC. We also demonstrated that two immune-related adverse events (irAEs) associated with camrelizumab can be managed with an anti-VEGF agent apatinib. This case not only highlights the importance of irAE management in patients treated with camrelizumab, but also demonstrates the potential of PD-1 antibody plus trastuzumab in HER2-positive GBC patients who have developed resistance to chemotherapy and trastuzumab-based targeted therapy.